1999
DOI: 10.1159/000015244
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal chromosome painting shows that genomic rearrangement between rat and mouse proceeds ten times faster than between humans and cats

Abstract: Reciprocal chromosome painting between mouse and rat using complete chromosome probe sets of both species permitted us to assign the chromosomal homology between these rodents. The comparative gene mapping data and chromosome painting have a better than 90% correspondence. The reciprocal painting results graphically show that mouse and rat have strikingly different karyotypes. At least 14 translocations have occurred in the 10–20 million years of evolution that separates these two species. The evolutionary rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 19 publications
3
54
0
Order By: Relevance
“…More detailed comparison between human and mouse were facilitated by the availability of whole genome sequences for both species (Guigo et al, 2003). The first genome-wide comparison between two rodent genomes (Mus musculus and Rattus norvegicus) by comparative chromosome painting was made in 1999 resulting in the almost simultaneous publication of papers by Grutzner et al (1999), Guilly et al (1999) and Stanyon et al (1999). Since then, over 100 rodent genomes from all major taxa have been analyzed resulting in the availability of comparative chromosomal maps and a more detailed analysis of karyotypic evolution in several of the major taxonomic groups (Table 1, Supplement Data 2).…”
Section: New Insights Into Karyotypic Evolution In Different Rodent Cmentioning
confidence: 99%
See 2 more Smart Citations
“…More detailed comparison between human and mouse were facilitated by the availability of whole genome sequences for both species (Guigo et al, 2003). The first genome-wide comparison between two rodent genomes (Mus musculus and Rattus norvegicus) by comparative chromosome painting was made in 1999 resulting in the almost simultaneous publication of papers by Grutzner et al (1999), Guilly et al (1999) and Stanyon et al (1999). Since then, over 100 rodent genomes from all major taxa have been analyzed resulting in the availability of comparative chromosomal maps and a more detailed analysis of karyotypic evolution in several of the major taxonomic groups (Table 1, Supplement Data 2).…”
Section: New Insights Into Karyotypic Evolution In Different Rodent Cmentioning
confidence: 99%
“…Only few representatives of other families have been included in comparative cytogenetic investigations. Nonetheless, comparative cytogenetic data show that high karyotypic reshuffling is characteristic for Myomorpha (for example, Stanyon et al, 1999) but that the elevated rate of chromosomal change was not accompanied by a rapid evolution of morphological features. Generally, the group has been reasonably well investigated by conventional cytogenetics, while 71 species have been investigated by comparative chromosome painting.…”
Section: Myomorphamentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by these chromosomal rearrangements in shaping the genomic architectures of eukaryotic species has been notably illustrated by comparative analyses between related species, including yeasts (Fischer et al 2000;Kellis et al 2003;Dujon et al 2004), plants (Schmidt 2002;Yogeeswaran et al 2005;Yu et al 2005), animals, and humans (Dutrillaux 1979;Stanyon et al 1999;Bailey et al 2002Bailey et al , 2004Stankiewicz and Lupski 2002;Jaillon et al 2004;Bourque et al 2005). Several experimental studies have shown that the fixation of translocations and duplications in populations of yeast maintained in continuous culture was obtained in response to growth-limited conditions and/or in competition experiments (Hansche et al 1978;Adams et al 1992;Brown et al 1998;Dunham et al 2002;Infante et al 2003;Colson et al 2004).…”
Section: R Eciprocal Translocations and Large Duplicationsmentioning
confidence: 99%
“…Each MPL 1, 2, 3, 4, 6 and 7 was painted by two different MMU probes, and ten out of the twelve MMU probes that painted these Indian spiny mouse chromosomes were hybridized to single chromosomes. in preparation), the long arm of rat chromosome 1 (Stanyon et al 1999) and the long arm of Chinese hamster chromosome 3 (Yang et al 2000). Thus, it is more likely that the ancestral type of MPL 6 was cleaved into two chromosomes, i.e.…”
Section: Chromosome Homology Between the Indian Spiny Mouse And The Lmentioning
confidence: 99%